(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Center For Research and Development (CRAD) is a web-based platform under School Management System 2 to manage all aspects of Research, such as research study documents, research defense, research festival, and research payment transactions. The research department of Bestlink College of the Philippines was experiencing manual transactions and spending more amount of time, but with the use of this system, the users will be able to use an automated system to find past research studies and check research payment transactions. The main objective of the researchers is to create a system that will help the staff and students complete the transactions faster by using an automated system instead of a manual. The researcher’s team results in more opportunities for clients that meet their needs and demands. The proponents successfully created a system that can truly help and eventually be able for research department to process their work. As a result, the client needs an automation system that is less time-consuming for research department transactions instead of a manual process. Discussion As interviews were performed by the team, Bestlink College of the Philippines Center For Research and Development (CRAD) has no automated system; it is time-consuming to manage transactions. The staff of the research department uses a manual way to process all the transactions, from collecting information to monitoring reports. In this research, the researcher will focus on developing a web-based for the research department. The main objective is to help the students, teachers, and staff provide a secure platform web-based system for automated transactions.